Review of typical biofuel for aviation alternative fuel purpose - Reksowadojo, Iman K. (ASEAN engineering journal)
Currently, along with ground used biofuel such as biodiesel, bioethanol has been utilizing widely over the world, alternative fuel for aviation purpose is increasing the consideration of researchers and governments as well as aviation industries. Several key priorities have been targeted for development aviation biofuel and three most important objectives have been identified which are decreasing fossil fuel reserves so that avoiding fluctuation of petroleum costs and reducing Greenhouse Gas (GHG) emissions. This paper presents a short review of researching activities in the field of aviation alternative fuel. Fatty Acid Esters (biodiesel or FAE), Fischer-Tropsch Synthetic Paraffinic Kerosene (FT-SPK) and Bio-derived Synthetic Paraffinic Kerosene (Bio-SPK) are the typical fuels. Research on physicochemical properties, ground engine test and flight demonstration were done by many authors as the investigation of using these biofuel for aviation. Research and development the biofuel for aviation promises a prospect and interesting work, however it also issues many challenges due to strict requirements of aviation fuel.